Isolated Components From Spider Venom Targeting Human Glioblastoma Cells and Its Potential Combined Therapy With Rapamycin - Caballero, Marcus; Barreto, Natalia; Bonfanti, Amanda Pires; Munhoz, Jaqueline; Rocha e Silva, Thomaz; Sutti, Rafael; Verinaud, Liana; Pinheiro de Mato, Felipe Cezar; Lanfredi, Guilherme Pauperio; Rapôso, Catarina (Frontiers in Molecular Biosciences, 2022)
Glioblastomas (GBs) are responsible for a higher mortality rate among gliomas, corresponding to more than 50% of them and representing a challenge in terms of therapy and prognosis. Peptide-based antineoplastic therapy is a vast and promising field, and these molecules are one of the main classes present in spider venoms. Recently, our research group demonstrated the cytotoxic effects of Phoneutria nigriventer spider venom (PnV) in GBs. The present study aimed to select the purified PnV-components with potential antineoplastic effects, as well as to compare different metabolic conditions. Human GB (NG97) cells were treated with the PnV fractions: F1 (less than 3 kDa), F2 (between 3 and 10 kDa), and F3 (greater than 10 kDa). After treatments, viability (MTT), proliferation (CFSE), death (Annexin V/propidium iodide-PI), and cell cycle (PI) assays were performed. The F1 and F2 fractions in acute periods (1 and 5 h) and low concentrations (0.1 and 1 μg/ml) showed more relevant effects and were repurified in subfractions (SF1–SF11); from these, SF3 and SF4 showed the most significant effects. The previous inhibition of mTOR by rapamycin had a synergistic effect with SFs, reducing cell viability even more significantly than the untreated control. Taken together, the results point to components present in SF3 and SF4 as potential prototypes for the development of new drugs for GB treatment and stimulate studies to use these compounds in combination therapy with a rapamycin-like activity. Future studies will be conducted to characterize, synthesize the molecules, and to evaluate the efficacy and safety in preclinical models.